Potentiality of Islamic Deposit Insurance System in Nigeria: A Lesson from Malaysia - Shamsuddeen Muhammad Ahmad; Salisu Hamisu (Sekolah Tinggi Ekonomi dan Bisnis Islam Lampung, 2019)
The financial crisis highlighted the need for deposit insurance regimes that effectively protect depositors and promote financial stability. Interest in Islamic deposit insurance is rising, incited by the growth of Islamic banking across the globe. The study examines the potentiality of Islamic deposit insurance scheme in Nigeria, considering Malaysian experience. To achieve its objective, this paper used both analytical and qualitative methods after thoroughly examining many relevant works of literature as well as empirical works. The study finds that Islamic deposits are covered separately from conventional deposits, with separate coverage for Islamic window, trust accounts, sole proprietorship, and partnership. It also provides coverage to various contracts, such as mudharabah, wadi`ah, qard and murabahah. Thus, Nigeria can tap the idea in promoting sound financial stability through Sharῑ’ah-compliant deposit insurance scheme. Finally, the paper concludes that to ensure a Shari`ah-compliant deposit insurance system, the government supposed to implement a proper approach, which could be different across jurisdictions, in light of differing Shari`ah interpretations or views from one jurisdiction to another.